First fullerene[60]-containing thermotropic liquid crystal - Chuard, Thierry; Deschenaux, Robert (My University, 1996)
The synthesis and liq.-cryst. and thermal properties of C60 functionalized through a methanofullerene structure by a framework contg. 2 cholesterol derivs. are reported. The compd. showed high thermal stability. [on SciFinder(R)]
Keywords: fullerene C60 cholesterol liq crystal property